Dual citizenship in Europe : from nationhood to societal integration - Faist, Thomas, 1959- (Ashgate, 2007)
In an age of terrorism and securitized immigration, dual citizenship is of central concern. The contributors to this timely volume examine policies regarding dual citizenship across Europe, covering a wide spectrum of countries. The case studies explore the negotiated character and boundaries of political membership and the fundamental beliefs and arguments which have shaped debates and policies on citizenship.